Private Houses under Central Bath (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2013)
During the latest excavations in Nora, Pula (Cagliari), University of Milan have found a big residential area in the central district of the roman city: before the III century A.D., houses are abandoned and covered by deep leveling layers, and then by the next Central Baths buildings. The pottery found in these layers is very important to date the end of this period and to understand the material culture of the roman people in Nora. This paper aims to be a synthesis of the preliminary excavations data, and a reflection on the targets of future research in this area.
Keywords: Nora